P0086FOCAL SEGMENTAL GLOMERULOSCLEROSIS AND TROMBOCYTOPENIA WITHOUT BLEEDING DIATHESIS: WHEN GENETICS MATTER. (6th June 2020) - Olivo, Elisa; Leonardi, Sabina; Di Maso, Vittorio; Artero, Mary Louise; Bianco, Francesco
Abstract: Background and Aims: A 45-year old patient presented to our renal unit because of increased serum creatinine (2 mg/dL), proteinuria (2g/24h collection) and haematuria; platelets were 12000/mcL. His family history was negative. He had already undergone cataract surgery and was wearing a hearing device. Alport syndrome was suspected and kidney biopsy performed. Light microscopy showed focal segmental glomerulosclerosis (FSGS), while immunofluorescence was negative. Electron microscopy was not available. No specific treatment was undertaken and he progressed to end-stage renal disease (ESRD) in 10 years. The patient chose peritoneal dialysis. He was considered at high risk of bleeding but the Tenchkoff catheter was inserted without problems. After 3 months he received kidney transplant and again no pathological bleeding occurred. Method: A genetic test was requested using next generation sequencing (NGS). Results: A mutation of myosin heavy chain 9 (MYH9) gene which encodes the non-muscle myosin heavy chain-IIA (NMMH-IIA) was found. This mutation is associated with thrombocytopenia and proteinuria; platelets are giant and display normal aggregation, even in those patients who have a very low count. Proteinuria can be mild or in the nephrotic range, with or without microhaematuria. Kidney involvement is highly heterogeneous and leads to ESRD in half of the cases. Light microscopy shows FSGS as the prevalent pattern whereas electron microscopy is characterized by podocyte foot process effacement. In fact, NMMH-IIA is expressed in podocytes and controls cytoskeleton and cell migration. The differential diagnosis with Alport disease is challenging because additional features of MYH9 mutation are sensorineural deafness and pre-senile cataract. For all these reasons, accurate kidney biopsy study, family history and genetics are decisive. Conclusion: Genetic testing has a pivotal role in understanding kidney diseases and should be more and more used.